Design and evaluation of mobile scenario based learning in the self-management of chronic pain. (January 2021) - Koulas, Ioannis; Billis, Antonis; Kousouri, Nikoletta; Vasilopoulos, Vasilis; Lykotsetas, Evangelos; Kola, Dimitris; Dafli, Eleni; Spachos, Dimitris; Bamidis, Panagiotis
Chronic pain is a lifelong issue, being one of the main causes of disability, affecting a great number of people worldwide, many of which often avoid seeking medical advice from pain experts and/or demonstrate poor adherence to their therapeutic plan. One of the most important steps in achieving a manageable course of disease, is the ability of self-management. We aimed at applying a method of systematic patient education and self-management through the use of Virtual Patients (VPs), a well-established method for educating medical doctors and students but never before targeting patients. Two VPs scenarios were designed, tested and evaluated by patients with rheumatic disorders, achieving a SUS score of 88/100 "Best Imaginable", alongside with positive reviews from the participants. The positive feedback from the patients supports the potential of VP educational paradigm to educate these patients and equip them with disease coping skills and strategies.